MORPHOLOGICAL AND PHAGOCYTIC PROPERTIES OF COELQMOCYTES OF THE EARTHWORM, MEGASCOLEX TRAVANCORENSIS - NAIR, K. VIJAYAKUMARAN; AJA, M.; JAVA, M.; NITHYA, J. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
The proportion of different types of coelomocytes and their morphological and cytological features and phagocytic properties in a native species of earthworm, Megascolex travancorensis have been studied. The three different classes of cells were noticed in the coelomic fluid of M trvancorensis were amoebocytes (Type I and Type II), granulocytes (Group I and Group II) and eleocytes. Amoebocytes are the most representative cells in the coelomic fluid in M travancorensis. All cells exhibited intense phagocytic activity during one hour of incubation. However, the amoebocytes were found to be more active in phagocytosis. The phagocytic activity of coelomocytes was found to increase as a function of time within observed time interval. Vacuolization in amoebocytes and formation of vesicular blebs on the membrane surface are signs of cellular aging.